Role of village-level workers in the process of political decentralisation - Saikia, Ashima Ahmed (Linguistics and Culture Review, 2021)
India, the second-largest democratic country in the world with about 1.21 billion people, among which all most half of the total population lives in the villages, and to the welfare of our nation, it is essential to improve the conditions of the villages. Therefore, rural development has become the first and foremost necessity for our country to develop. In India for all-round development of the rural areas the village level worker is responsible. They are recruited by a district-level selection committee chaired by the district collector. Usually, there are ten village-level workers in a development block. They must have passed the matriculation examination and the age limit is 24. They must belong to a rural area. From planning to implementing various policies for the rural people, from making aware the rural poor to ensuring their participation in them are the primary duties of the village level workers.